Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content: 1. Emotional intelligence’ among secondary school teachers in Bahri locality Ghada Al- Ameen Ahmed 2. The reality of the practice of the teachers of the lower basic stage of blended education and its reflection on the application of differentiated education from their point of view in the schools of the Directorate of Education in South Hebron Ferial Abdulaziz Mohammad Amro 3. Developing the performance of female educational supervisors in Jazan region in the view of contemporary trends of educational supervision Aishah Mahah Safhi 4. Home schooling: It’s justifications and importance of its application applying it in Saudi Arabia in light of Islamic Educational Principles Ali Abdullah Ahmed Al-Zahrani 5. Psychological well-being and its relationship to religious behavior among students of Sultan Qaboos University - Sultanate of Oman Hilal Salim Sulaiman Alabri 6. Cognitive Bias and its Relationship to Learning Motivation among Umm Al-Qura University Students Dayana Fahmi Ali Hammad - Shuruq Abdullah Muhammad Baothman 7. The level of Insurance awareness among private school teachers in the capital’s Secretariat Sana’a Mrs. Yasmine Yehia Abdel-Qader Al-Khatari, Co-Prof. Eman Saleh Al-Sanabani